Effects of Near Addition Lenses and Prisms on Accommodative Microfluctuations in Chinese Children. Issue 5 (May 2016) - Lin, Huiling; Drobe, Björn; Jin, Wanqing; Lin, Meng; Chen, Yunyun; Chen, Hao
ABSTRACT: Purpose: To investigate the effects of different near addition lenses and prisms on accommodative microfluctuations (AMFs) in Chinese early-onset myopic (EOM) and emmetropic (EMM) children. Methods: Twenty-one EMM and 27 EOM children aged between 9 and 14years participated in the study. At near, 23 children were exophoric (exo, <0 Δ), and 25 were esophoric (eso, ≥0 Δ). The AMFs and phoria through multiple addition lenses (−1.00, 0, +1.00, +2.00, and +3.00D on each eye) and prisms (base-in prism power: 3 Δ, 2 Δ, 1 Δ; and base-out prism power: 1 Δ and 2 Δ on each eye) were measured at 25cm under binocular viewing conditions with a Grand Seiko WAM-5500 auto-refractor and a modified Thorington card. Results: Higher AMFs were found in EOM than in EMM (EOM, 0.19±0.06D; EMM, 0.16±0.03D; p=0.035). Plus additions from +1.00 to +3.00D reduced the AMFs in both EMM and EOM, except +3.00D for EMM. In both refractive groups, −1.00D additions increased AMFs. Esophores showed greater AMFs compared with exophores (esophores, 0.20±0.01D; exophores, 0.16±0.01D; p=0.012). Prisms increased the AMFs in EMM and did not alter the AMFs in EOM. Conclusions: Microfluctuations of accommodation decreased with plus addition lenses and increased with negative addition lenses. Plus addition lenses of +2.00 to +3.00D for EOM and +2.00D for EMM decreased AMFs the least at a 25-cm working distance. Esophores had higher AMFs than exophores, indicating that phoria status influences AMFs.